2010
DOI: 10.1111/j.1439-037x.2009.00414.x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Application of Putrescine Ameliorates the Effect of High Temperature in Gossypium hirsutum L. Flowers and Fruit Development

Abstract: Polyamines have been shown to stimulate fruit set and the initial phase of fruit development in several crops. The effect of exogenous application of putrescine on ovary development and seed set of cotton under high temperature stress was investigated under controlled environmental conditions. Putrescine was applied to floral buds of cotton, 24 h prior to anthesis, and caused a significant increase in putrescine content of cotton ovaries collected at anthesis compared with the control treatment. However, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 30 publications
1
19
1
Order By: Relevance
“…[52][53][54] Several other studies showed that exogenous application of different PAs helped to overcome the stress effect to some extent. 55,56 The effect of salinity stress on the activation of ADC, as well as its increased transcript level was observed in NaCltolerant rice cultivars exposed to 150 mM NaCl for 12 h. 57 Salt and osmotic stress induced the accumulation of Put and Spd and increased ADC activity in the roots and leaves of lupine (Lupinus luteus) seedlings and in apple (Malus domestica). 58,59 Increased 63 Drought stress in rice also increased bound and free Put with increased resistance.…”
Section: Metal Stressmentioning
confidence: 99%
“…[52][53][54] Several other studies showed that exogenous application of different PAs helped to overcome the stress effect to some extent. 55,56 The effect of salinity stress on the activation of ADC, as well as its increased transcript level was observed in NaCltolerant rice cultivars exposed to 150 mM NaCl for 12 h. 57 Salt and osmotic stress induced the accumulation of Put and Spd and increased ADC activity in the roots and leaves of lupine (Lupinus luteus) seedlings and in apple (Malus domestica). 58,59 Increased 63 Drought stress in rice also increased bound and free Put with increased resistance.…”
Section: Metal Stressmentioning
confidence: 99%
“…Regarding polyamine metabolism in cotton under abiotic stresses, Bibi et al (2010) [18] reported that application of PUT on cotton flowers resulted in increases in PUT levels of the ovary and seed set efficiency under conditions of heat stress, while SPD and SPM concentrations were significantly decreased. Considering that wa-ter-deficit stress is the most important abiotic factor affecting crop production in almost 40% of cultivated areas around the world [19] and that drought events are projected to intensify in the future [20], it is imperative that research efforts should be focused on finding ways to ameliorate the consequences of water-deficit stress.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Akiyama and Jin (2007) have demonstrated that the OsADC1 gene is regulated in an essentially chilling-specific manner, possibly associated with increased Put accumulation in rice. PAs have also been shown to stimulate fruit set and the initial phase of fruit development in several crops (Iqbal et al 2006b,c, Bibi et al 2010). In the present study, chilling increased Put concentration only in the salt intolerant, whereas Spm concentration in both wheat cultivars when grown under salt stress.…”
mentioning
confidence: 99%